UPAYA UNIT LALU LINTAS DALAM PENANGANAN KECELAKAAN LALU LINTAS MELALUI RESTORATIVE JUSTICE DI WILAYAH HUKUM POLSEK NUSA PENIDA - Dewa Putra, Putu Aditya (Kerta Dyatmika, 2025)
Traffic accidents are incidents that require resolution between the involved parties. In addition to litigation processes, a non-litigation approach known as Restorative Justice has recently been implemented within the police force as an alternative dispute resolution mechanism. This study aims to examine the efforts of the Traffic Unit in handling traffic accidents through restorative justice within the jurisdiction of Nusa Penida Police Sector, as well as to identify the obstacles encountered in its implementation. The research employs an empirical juridical method with a descriptive approach by conducting direct field research through interviews with relevant informants. The findings indicate that the restorative justice process involves several stages, namely: identifying cases eligible for restorative settlement, conducting mediation between the involved parties, restoring the losses suffered by the victim, and evaluating and monitoring the agreement’s outcomes. Obstacles in the implementation include the lack of awareness and understanding of the restorative justice concept among both law enforcement officers and the public, resistance from involved parties who may be unwilling to participate in the restorative process, and limited resources including time, personnel, and the availability of adequately trained mediators or facilitators. The study concludes that although restorative justice offers an effective alternative in handling traffic accidents, its successful application requires enhanced understanding, adequate resource allocation, and collaborative support from all stakeholders.